Profile and aetiology of children diagnosed with auditory processing disorder (APD). - Dawes, P; Bishop, D; Sirimanna, T; Bamiou, D (2008)
OBJECTIVE: Auditory processing disorder (APD) is characterised by listening difficulties despite a normal audiogram. APD is becoming ever more widely diagnosed in children, though there is a controversy over definition, diagnosis and aetiology. This study sought to describe presenting features and investigate aetiological factors for children diagnosed with APD compared to those for whom APD was excluded. METHODS: Medical notes for children referred to a specialist hospital-based APD clinic were reviewed in relation to presenting features and potential aetiological factors. RESULTS: 32 children diagnosed with APD and 57 non-APD children were compared. They reported similar symptoms and similarly had high rates of co-morbid learning problems. No aetiological factor (including history of otitis media, adverse obstetric history or familial history of listening problems) predicted APD group membership. CONCLUSIONS: Children identified with APD on the basis of commonly used APD tests cannot be distinguished on the basis of presenting features or the aetiological factors examined here. One explanation is that learning problems exist independently of auditory processing difficulties and the aetiological factors do not have a strong causal role in APD. However, no gold standard for APD testing exists and an alternative explanation is that the commonly used APD tests used as selection criteria in this study may be unreliable.